Frustrated tunnelling ionization during strong-field fragmentation of D3+ - McKenna, J.; Sayler, A. M.; Gaire, B.; Kling, Nora G.; Esry, B. D.; Carnes, K. D.; Ben-Itzhak, I. (My University, 2012)
We reveal surprisingly high kinetic energy release in the intense-field fragmentation of D3+ to D+ + D+ + D with 1016 W cm−2, 790 nm, 40 fs (and 7 fs) laser pulses. This feature strongly mimics the behaviour of the D+ + D+ + D+ channel. From the experimental evidence, we conclude that the origin of the feature is due to frustrated tunnelling ionization, the first observation of this mechanism in a polyatomic system. Furthermore, we unravel evidence of frustrated tunnelling ionization in dissociation, both two-body breakup to D + D2+ and D+ + D2, and three-body breakup to D+ + D + D.